2017
DOI: 10.1002/lary.26518
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of intratympanic gadolinium helps differentiate vestibular migraine from Ménière disease

Abstract: 4 Laryngoscope, 127:2382-2388, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 35 publications
0
31
1
1
Order By: Relevance
“… 33 30 MD IT ECoG ECoG Sun et al . 34 30 VM, MD IT PTA, VEMP PTA, VEMP (partial) Seo et al . 35 26 MD IT PTA, ECoG, VEMP PTA, ECoG: Yamamoto et al .…”
Section: Discussionmentioning
confidence: 99%
“… 33 30 MD IT ECoG ECoG Sun et al . 34 30 VM, MD IT PTA, VEMP PTA, VEMP (partial) Seo et al . 35 26 MD IT PTA, ECoG, VEMP PTA, ECoG: Yamamoto et al .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are 5 large (53-74 patients) 113-117 and another 25 smaller case series that evaluated MD patients with delayed postcontrast MRI. 118-142 These data revealed that distention of the endolymphatic space in the cochlea and vestibule (ELH) is commonly identified in patients with definite MD and more frequently than other causes of SNHL or vertigo. However, this finding is not present in all patients with MD, and there remains variability within imaging protocols and proposed grading/assessment systems.…”
Section: Guideline Key Action Statementsmentioning
confidence: 97%
“…Although several EH assessment techniques exist [11,12], this review combined the results of the most commonly reported grading method for hydrops MR evaluation in literature [13,14]. This method categorizes hydrops in either "mild" or "significant."…”
Section: Estimation Of Eh and Symptom Prevalencesmentioning
confidence: 99%
“…In total, 69 publications were selected after database searching and citation and reference retrieval for estimating the prevalence of EH and neuro-otologic symptoms in different types of study populations [3,9,12,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Based on the available data, three vestibular disorders were selected for prevalence estimation: (1) The clinical diagnosis of Menière's disease based on diagnostic criteria (Table 1) [16], (2) The diagnosis of vestibular schwannoma confirmed by MRI, (Table 2), and (3) The clinical diagnosis of vestibular migraine based on diagnostic criteria (Table 3) [17].…”
Section: Study Selectionmentioning
confidence: 99%